2014
DOI: 10.1186/1752-1947-8-310
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear osteoma causing progressive facial nerve weakness: a case report

Abstract: IntroductionFacial nerve weakness is most commonly due to Bell’s palsy or cerebrovascular accidents. Rarely, middle ear tumor presents with facial nerve dysfunction.Case presentationWe report a very unusual case of middle ear osteoma in a 49-year-old Caucasian woman causing progressive facial nerve deficit. A subtle middle ear lesion was observed on otoscopy and computed tomographic images demonstrated an osseous middle ear tumor. Complete surgical excision resulted in the partial recovery of facial nerve func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…4 We reviewed MEDLINE database and only three other cases reported since then. 2,5,6 Including the patient in this study there were 25 males and 15 females with a male predominance 1.67:1. The age of patients ranging from 5 year old to 57 years old with mean age of 29.3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 We reviewed MEDLINE database and only three other cases reported since then. 2,5,6 Including the patient in this study there were 25 males and 15 females with a male predominance 1.67:1. The age of patients ranging from 5 year old to 57 years old with mean age of 29.3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that middle ear osteomas may present with other manifestations such as vestibular manifestations, facial palsy, mixed hearing loss, Tullio phenomenon, otorrhea, discharge and tinnitus. 3,[6][7][8] CT scan is the recommended complementary image as it defines the extent and probable origin of the lesion also detecting any secondary manifestations of the tumor. 2 The promontory is the most commonly involved site, followed by incus, pyramidal process, and the anterolateral wall of the epitympanum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions arising from temporal bones are considered rare occurrence (8). Osteomas of external auditory canal are rare, but still most common tumors of temporal bones (8). Shah et al report their incidence to be 0.05% of complete otologic surgery (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Middle-ear osteomas are very rare and may present with various clinical findings including conductive or mixed hearing loss, facial nerve dysfunction, vertigo and otitis media according to the site of involvement in the temporal bone. 4 Herein, the author reports a very rare case of osteoma of the promontory that mimicked otosclerosis, causing progressive conductive hearing loss and tinnitus by limiting stapes mobility, which is an uncommon condition.…”
Section: Introductionmentioning
confidence: 99%